Glucosidase II and N-glycan mannose content regulate the half-lives of monoglucosylated species in vivo - Stigliano, Ivan Daniel (2011)
Glucosidase II (GII) sequentially removes the two innermost glucose residues from the glycan (Glc3Man9GlcNAc2) transferred to proteins. GII also participates in cycles involving the lectin/chaperones calnexin (CNX) and calreticulin (CRT) as it removes the single glucose unit added to folding intermediates and misfolded glycoproteins by the UDPGlc: glycoprotein glucosyltransferase (UGGT). GII is a heterodimer in which the á subunit (GIIα) bears the active site, and the β subunit (GIIβ) modulates GIIα activity through its C-terminal mannose 6-phosphate receptor homologous (MRH) domain. Here we report that, as already described in cell-free assays, in live Schizosaccharomyces pombe cells a decrease in the number of mannoses in the glycan results in decreased GII activity. Contrary to previously reported cell-free experiments, however, no such effect was observed in vivo for UGGT. We propose that endoplasmic reticulum α-mannosidase-mediated N-glycan demannosylation of misfolded/slow-folding glycoproteins may favor their interaction with the lectin/chaperone CNX present in S. pombe by prolonging the half-lives of the monoglucosylated glycans (S. pombe lacks CRT). Moreover, we show that even N-glycans bearing five mannoses may interact in vivo with the GIIβ MRH domain and that the N-terminal GIIβ G2B domain is involved in the GIIα-GIIβ interaction. Finally, we report that protists that transfer glycans with low mannose content to proteins have nevertheless conserved the possibility of displaying relatively long-lived monoglucosylated glycans by expressing GIIβ MRH domains with a higher specificity for glycans with high mannose content.